PENGARUH UKURAN PERUSAHAAN, KONSENTRASI PASAR AUDIT, DAN CLIENT IMPORTANCE TERHADAP KUALITAS AUDIT - Reza Armanda Ramadhan, (2022)
This research is a quantitative study aimed to examine the effect of company size, audit market concentration, and client importance on audit quality. The population in this study are financial companies listed on the Indonesia Stock Exchange in 2018-2020. The sample in this study obtained 95 financial companies which were selected using the purposive sampling method. In this study, audit quality is measured by earning surprise benchmark, company size measured by Ln total asset method, audit market concentration measured by number of clients Big 4 audit firms, and client importance is measured by Ln total asset method divided by total assets in Ln of client audited by an audit firm. Hypothesis testing in this study used Logistics Regression Analysis using SPSS analysis tool with a significant level of 5%. The result of hypothesis testing showed that (1) company size have a significant positive effect on audit quality, (2) audit market concentration have a significant negative effect on audit quality, (3) client importance have no effect on audit quality.